2022
DOI: 10.1371/journal.pone.0275130
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of game-based virtual reality phone application and online education on knowledge, attitude and compliance of standard precautions among nursing students

Abstract: Game-based virtual reality phone applications can create a realistic environment to prepare for clinical applications and improve students’ knowledge of and compliance with standard precautions. An experimental study was performed among 126 nursing students’ from the third and fourth nursing levels to determine the effect of online education and game-based virtual reality phone applications related to standard precautions. Students were divided randomly into two groups; the experimental group used online educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…This result aligns with a study conducted in Northern Cyprus, where participants showed inadequate knowledge ( 27 ) and contrasted with international studies that showed the students had inadequate knowledge of NSI ( 8 , 28 , 29 ). Such a high score indicates that nursing students in the current study had sufficient knowledge regarding NSI, confirming that the nursing school offered special courses such as infection control to students before starting clinical practice ( 30 ). More than half of the nursing students were senior students and had previous education about NSI, meaning they have high exposure to the causes and risk factors of needle stick injuries.…”
Section: Discussionsupporting
confidence: 68%
“…This result aligns with a study conducted in Northern Cyprus, where participants showed inadequate knowledge ( 27 ) and contrasted with international studies that showed the students had inadequate knowledge of NSI ( 8 , 28 , 29 ). Such a high score indicates that nursing students in the current study had sufficient knowledge regarding NSI, confirming that the nursing school offered special courses such as infection control to students before starting clinical practice ( 30 ). More than half of the nursing students were senior students and had previous education about NSI, meaning they have high exposure to the causes and risk factors of needle stick injuries.…”
Section: Discussionsupporting
confidence: 68%
“… 32 Providing in-service education is important for medication errors decreasing and infection control that allows the nurses to adapt with recent guidelines of medication, and new administration techniques. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Games are already widely used in the academic environment as an educational tool, mainly in undergraduate medical and nursing courses 4 5 9 10 20. However, to the best of our knowledge, reports have yet to be published on game-based strategies in Collaborative LS.…”
Section: Discussionmentioning
confidence: 99%